CSF2RB Is a Unique Biomarker and Correlated With Immune Infiltrates in Lung Adenocarcinoma - Zhu, Ningning; Yang, Yueyang; Wang, Haitong; Tang, Peng; Zhang, Hongdian; Sun, Haiyan; Gong, Lei; Yu, Zhentao (Frontiers in Oncology, 2022)
Background: The tumor microenvironment plays an important role in the occurrence and development of tumors. However, there are gaps in understanding the molecular and cellular interactions between tumor cells and the immune tumor microenvironment (TME). The aim of this study was to identify a novel gene that played an important role in the tumor microenvironment of lung adenocarcinoma (LUAD). Methods: The gene expression profile and clinical data for LUAD were downloaded from the TCGA database. First, we used the ESTIMATE algorithm to evaluate the immune and stromal scores accordingly. And we analyzed differentially expressed immune-related genes (IRGs) in the high and low immune/stromal score groups. Then we used protein-protein interaction network (PPI network) and a univariate Cox regression analysis to identify the hub gene. After that, we analyzed the relationship between CSF2RB expression and TNM stage/prognosis. Furthermore, Gene set enrichment analysis (GSEA) was used to analyze the pathway regulated by CSF2RB and the Pearson correlation analysis method was used to analyze the correlation between the CSF2RB and immune cells. Finally, we used western blot, Real-Time Quantitative PCR (RT-qPCR) and immunohistochemistry (IHC) to validate CSF2RB expression in cancer and para-cancerous tissues. Results: We identified that CSF2RB played an important role in the tumor microenvironment of LUAD. The expression of CSF2RB in tumor tissues was lower than normal tissues. Furthermore, Kaplan-Meier plotter showed that low CSF2RB expression was associated with poor survival and Multivariate COX regression analysis revealed that the CSF2RB gene was an independent risk factor for prognosis, independent of whether patients received chemotherapy or radiotherapy. More importantly, high expression of CSF2RB was related to early T, N and clinical stages. GSEA analysis revealed CSF2RB associated with diverse immune-related pathways, including T cell receptor signaling pathway, Toll like receptor signaling pathway, B cell receptor signaling pathway et al. CSF2RB expression levels were also positive related with the levels of infiltrating CD4+ T cells, macrophages, NK cells, and Monocytes in LUAD. Finally, tumor tissues from LUAD patients were used for the assessment CSF2RB expression. It was significantly lower in tumor sites than adjacent normal tissues, which was consisted with data analysis.